People's Republic of China-Hong Kong Special Administrative Region : 2012 Article IV Consultation Discussions. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
The Hong Kong Special Administrative Region (SAR)'s healthy labor market and supportive fiscal policy helped its domestic economy's resilience, while its gross domestic product (GDP) growth was marginally slow owing to its weak external environment. Its fiscal policy has been effective in reducing output volatility and providing timely support to help counter the impact from slowing external demand. The authorities have taken appropriate macroprudential measures to help safeguard the banking system, which should continue to be fine-tuned in line with evolving risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet